(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the current problems of modernization of the mahalla institution in Uzbekistan, modern approaches to the analysis of the activities of local self-government bodies, as well as the peculiarities of the organization of multi-ethnic, religious communities in the years of independence.